The addition of vitamin C in tris–egg yolk extender maintained Sapera goat semen quality in 5° C storage - Pahlevy, Jolly Rifqi; Ratnani, Hermin; Restiadi, Tjuk Imam; Fikri, Faisal; Saputro, Amung Logam; Agustono, Bodhi (Ovozoa: Journal of Animal Reproduction, 2022)
Goats are small ruminants that are reared by the rural community for financial income and nutrition. This study was aimed to determine the effect of vitamin C addition in tris–egg yolk extender on the lifespan of Sapera goat spermatozoa stored in 5o C. Semen was collected from 1.5 years old Sapera male goat. The ejaculates were diluted in Tris-egg yolk (T-EY) extender added with 0, 0.2, 0.3, and 0.4 g vitamin C/mL extender for T0, T1, T2, and T3 groups, respectively. The spermatozoa motility, viability, and morphological abnormality were assessed along with storage at 5° C. The result showed that spermatozoa motility was the highest (p <0.05) in T1 compared to other groups and qualified for AI use for up to 72 hours. In 24 hours storage, the spermatozoa viability was not significantly different (p >0.05) among the groups. The spermatozoa viability in the T1 group was the highest (p <0.05) among the groups along 48-96 hours of storage. The spermatozoa morphological abnormalities of the T1 group was the lowest (p <0.05) compared to other treatment groups in the range of 24-72 hour storage. In the control group (T0), the less than 5% spermatozoa morphological abnormalities (qualified for artificial insemination) were only in the 24 hours storage, while those of the T1 group were up to 72 hours. It could be concluded that the addition of 0.2 g vitamin C/100 mL T-EY extender maintained the quality of Sapera goat semen for 72 hours at 5°C.